Specific interaction between fluorine atoms and thiol groups accounting for higher domain purity and photostability in narrowband BHJ systems. Issue 14 (10th June 2019) - Zhou, Weihua; Yu, Zoukangning; Zhang, Ming; Zhang, Lifu; Yin, Jingping; Ai, Qingyun; Huang, Liqiang; Liu, Feng; Zeng, Jianrong; Chen, Yiwang
ABSTRACT: In order to explore the role of fluorine atoms on photostability as well as morphology control of active layer in the presence of 1, 4‐butanedithiol (BT), the four polymers with or without fluorine atoms in the backbones including polythieno[3, 4‐b]thiophene/benzodithiophene, poly[(4, 8‐bis‐(2‐ethylhexyloxy)‐benzo(1, 2‐b:4, 5‐b9)dithiophene)‐2, 6‐diyl‐alt‐(4‐(2‐ethylhexanoyl)‐thieno[3, 4‐b]thiophene‐)‐2‐6‐diyl)], poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b;4, 5‐b′]dithiophene‐2, 6‐diyl‐alt‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3, 4‐b]thiophene‐)‐2‐carboxylate‐2‐6‐diyl)], and poly[4, 8‐bis‐(2‐ethyl‐hexyl‐thiophene‐5‐yl)‐benzo[1, 2‐b:4, 5‐b0]dithiophene‐2, 6‐diyl]‐alt‐[2‐(20‐ethyl‐hexanoyl)‐thieno [3, 4‐b]thiophen‐4, 6‐diyl] were selected for comparison. It is found that the specimens containing fluorine atoms in polymer backbones showed of higher stability after illumination for 1 h in the presence of BT additive, contributing to the higher domain purity. The specific interaction between fluorine atoms and thiol groups was demonstrated by the appearance of novel absorption peak at 2663.1 cm −1, in addition to the broadening of peak at 2556.2 cm −1 ascribing to SH stretching vibration as confirmed by Fourier transform infrared (FTIR) spectroscopy. The finding may guide the accurate use of thiols as effective solvent additive in morphology and stability optimization. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 941–951 Abstract : Specific interaction between fluorine and thiol groups confirmed by Fourier transform infrared spectroscopy accounts for enhanced domain purity and photostability in the bulk heterojunction systems containing fluorine atoms in the backbone. This novel finding could guide the appropriate use of thiols as solvent additives to optimize the morphology of the active layer in other solar cells.